Business and Management Impact Assessment in Research Excellence Framework 2014: Analysis and Reflection. (5th September 2016) - Kellard, Neil M.; Śliwa, Martyna
Abstract : The evaluation of research impact is likely to remain an important element of research quality audits in the UK for the foreseeable future. With this paper, we contribute to debates on impact and relevance of business and management studies research through an analysis of Research Excellence Framework 2014 impact scores within the business and management unit of assessment. We offer insights into the organizational contexts of UK business schools within which impact is produced, drawing attention to the issues of linkages with research intensity, grant income generation, research team size, career stage and gender of academics, and whether impact activity is focused on private or public sector organizations and national or international reach. We put forward recommendations for managers responsible for business schools and higher education policymakers regarding management and organizational policies and processes, as well as possible changes to the rules guiding future research excellence audits.